Interior of the Great Cave Gasparee, Trinidad. B.W.I. - (:unkn) unknown (James Book Store, 2010)
This multiple view cards vintage postcard displays various scenes inside the Great Cave at Gasparee Caves on Gasparee Island, also known as Gaspar Grande, an island made of limestone off the north–west coast of Trinidad. Most of the photographs feature stalactites and stalagmites formed as a result of a combination of wave action, rainfall and percolating ground-water dissolving the limestone. The caves' formations are reflected in their pools. The caves are one of Trinidad’s tourist attractions. Postcard number S2 - 7.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Stalactites and stalagmites--Trinidad and Tobago; Caves--Trinidad and Tobago; Islands--Trinidad and Tobago; Gaspar Grande; Gasparee